2013
DOI: 10.1073/pnas.1213283110
|View full text |Cite
|
Sign up to set email alerts
|

Function of Piwi, a nuclear Piwi/Argonaute protein, is independent of its slicer activity

Abstract: The Piwi protein subfamily is essential for Piwi-interacting RNA (piRNA) biogenesis, transposon silencing, and germ-line development, all of which have been proposed to require Piwi endonuclease activity, as validated for two cytoplasmic Piwi proteins in mice. However, recent evidence has led to questioning of the generality of this mechanism for the Piwi members that reside in the nucleus. Drosophila offers a distinct opportunity to study the function of nuclear Piwi proteins because, among three Drosophila P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 30 publications
1
55
0
Order By: Relevance
“…Due to the limitations of plasmid transfections, we were unable to show that a Slicer-defective PIWI transgene could rescue reporter gene silencing after PIWI knockdown in OSS cells (data not shown). However, others have previously shown that Drosophila PIWI deficient in Slicer activity can rescue TE silencing after PIWI knockdown in OSCs (Saito et al 2010) and rescue piwi mutant sterility (Darricarrere et al 2013). This contrasts with mouse MIWI and MILI proteins that do require Slicer activity for TE silencing (De Fazio et al 2011;Reuter et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limitations of plasmid transfections, we were unable to show that a Slicer-defective PIWI transgene could rescue reporter gene silencing after PIWI knockdown in OSS cells (data not shown). However, others have previously shown that Drosophila PIWI deficient in Slicer activity can rescue TE silencing after PIWI knockdown in OSCs (Saito et al 2010) and rescue piwi mutant sterility (Darricarrere et al 2013). This contrasts with mouse MIWI and MILI proteins that do require Slicer activity for TE silencing (De Fazio et al 2011;Reuter et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear which of these mechanisms dominate in gonadal cells, and how many piRNAs are required to manifest target regulation. Despite the fact that Drosophila PIWI retains the catalytic residues which exhibit "Slicer" endonucleolytic activity (Lau et al 2006;Saito et al 2006;De Fazio et al 2011;Reuter et al 2011), this activity is not required for TE repression nor loading of piRNAs into PIWI (Saito et al 2010;Darricarrere et al 2013). If piRNAs require perfect base-pairing for efficient targeting and silencing, this would partially explain the preference of piRNAs targeting TEs over genes.…”
Section: Introductionmentioning
confidence: 99%
“…Localization of Piwi within the nuclei of nurse cells and the oocyte has been well established using whole-mount ovary preparations (Brennecke et al 2007;Klattenhoff et al 2009;Wang and Elgin 2011;Darricarrère et al 2013;Dufourt et al 2014); however, these data have not yielded conclusive evidence that Piwi physically associates with oocyte chromatin. Therefore, we used ovaries from wild-type females to prepare chromosome spreads, a technique in which cytosolic proteins are removed as well as nuclear proteins that are not bound to chromatin (Peters et al 1997;Khetani and Bickel 2007).…”
Section: Piwi Protein Stably Associates With Oocyte Chromosomesmentioning
confidence: 97%
“…This phenotype is also seen in flam mutant flies, suggesting the cooperative roles of Piwi and piRNAs (Desset et al, 2008;Pelisson et al, 1994). Interestingly, mutational analyses and functional studies indicate that the nuclear localization of Piwi is required for TE silencing in fruit flies and ovarian somatic cell line, whereas its slicer activity is not, suggesting that the silencing step occurs in the nucleus and is not a consequence of the direct cleavage of TE mRNAs (Cox et al, 2000;Darricarrere et al, 2013;Klenov et al, 2011;.…”
Section: The Role Of Piwimentioning
confidence: 99%